2020
DOI: 10.3389/fneur.2020.574004
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Neuropsychological Deficits, Central Nervous System Involvement, and Brain Stem Affection After COVID-19—A Case Series

Abstract: Objective: The affection of both the peripheral (PNS) and central nervous system (CNS) by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been assumed to play a direct role in the respiratory failure of patients with Corona virus disease 2019 (COVID-19) through affection of medullary cardiorespiratory centers resulting in neurological complications and sequelae. Methods: We used a multimodal electrophysiological approach combined with neuropsychological investigations to study functional alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
(34 reference statements)
1
20
0
1
Order By: Relevance
“…To date, most studies have relied on brief cognitive screening measures or small case series rather than detailed neuropsychological test batteries in samples of sufficient size to permit detection of patterns of impairment and associated disease and treatment characteristics( (13) , (14) , (15) , (16) , (17) ). Much remains to be learned about the nature and severity of cognitive and psychiatric functioning across patients of varying disease severity and at various time points over the course recovery from COVID-19( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have relied on brief cognitive screening measures or small case series rather than detailed neuropsychological test batteries in samples of sufficient size to permit detection of patterns of impairment and associated disease and treatment characteristics( (13) , (14) , (15) , (16) , (17) ). Much remains to be learned about the nature and severity of cognitive and psychiatric functioning across patients of varying disease severity and at various time points over the course recovery from COVID-19( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurological symptoms from COVID-19 have been detected weeks past the acute phase (Groiss et al 2020 ). Through the use of electrophysiological studies (e.g., electroencephalography), Groiss et al found that both the peripheral nervous system and the central nervous system were affected by SARS-CoV-2 in 4 male patients.…”
Section: Covid-19 Pathologymentioning
confidence: 99%
“…Through the use of electrophysiological studies (e.g., electroencephalography), Groiss et al found that both the peripheral nervous system and the central nervous system were affected by SARS-CoV-2 in 4 male patients. Delirium was seen in these patients and cognition was impaired even after delirium passed (Groiss et al 2020 ). Another study showed 4 children with COVID-19 who displayed similar neurological symptoms (e.g., encephalopathy, headache, brainstems with signs of dysarthria/dysphagia, meningism, cerebellar ataxia, muscle weakness, reduced reflexes, and lesions in the splenium of corpus callosum) had little to no respiratory symptoms (Abdel-Mannan et al 2020 ).…”
Section: Covid-19 Pathologymentioning
confidence: 99%
“…More recently, a relation between intestinal inflammation (by fecal calprotectin determination) and the incidence of fecal SARS-CoV-2 RNA in hospitalized individuals has been reported [ 82 ]. Pro-inflammatory intermediates in the GI tract can form a path to the brain through the vascular or lymphatic system [ 83 , 84 , 85 ]. Additionally, virus-welded gut inflammation may trigger cognitive functions via the vagal nerve ( Figure 4 ).…”
Section: The Correlation Between Gastrointestinal and Neurological Symptoms Induced By Sars-cov-2mentioning
confidence: 99%